Abnormal fractional Amplitude of Low-Frequency Fluctuation in chronic ketamine users. (October 2022) - Zhong, Jun; Wu, Huawang; Wu, Fengchun; He, Hongbo; Zhang, Zhaohua; Huang, Jiaxin; Cao, Penghui; Fan, Ni
Highlights: Our study found abnormal fALFF in multiple brain areas in chronic ketamine users, which indicated the changes of intrinsic spontaneous neural activity in multiple brain areas. The changes of fALFF were associated with the severity of ketamine use in chronic ketamine users. The changes of fALFF were associated with cognitive impairment in chronic ketamine users. Abstract: Background: Ketamine has become a major substance of abuse worldwide. Nevertheless, The long-term effects of ketamine use on intrinsic spontaneous neural activity remain unknown. Objectives: In the present study, rs-fMRI was used to explore whether chronic ketamine use changes the intrinsic spontaneous neural activity, and whether the intrinsic spontaneous neural activity changes in chronic ketamine users(CKUs) are associated with cognitive impairments observed in chronic ketamine users. Methods: 28 CKUs and 30 healthy controls(HC) were enrolled. The fractional amplitude of low-frequency fluctuations (fALFF) was measured to evaluate the intrinsic spontaneous neural activity in multiple brain regions. Cognitive alterations were assessed using MATRICS Consensus Cognitive Battery (MCCB). Results: CKUs showed higher fALFF in the right parahippocampal gyrus(PHG), right anterior cingulate cortex(ACC), left cerebellar vermis, left posterior cingulate cortex(PCC), bilateral caudate, and lower fALFF in the right middle occipital gyrus(MOG), left cuneus, right precuneus. The fALFF in the right PHG, left cerebellar vermis, bilateral caudate, right ACC of CKUs presented a negative correlation with the average quantity of ketamine use/day(g) and estimated total ketamine consumption. The fALFF in left PCC had a negative correlation with the average quantity of ketamine use/day(g). Speed of processing on MCCB presented a negative correlation with the fALFF in the right MOG. Conclusion: Our study found abnormal fALFF in multiple brain areas in CKUs, which indicated the changes of intrinsic spontaneous neural activity in multiple brain areas. The changes of fALFF were associated with the severity of ketamine use and cognitive impairment in CKUs.